Biochemical toxicity and transcriptome aberration induced by dinotefuran in Bombyx mori. (15th August 2022) - Xu, Shiliang; Hao, Zhihua; Li, Yinghui; Zhou, Yanyan; Shao, Ruixi; Chen, Rui; Zheng, Meidan; Xu, Yusong; Wang, Huabing
Abstract: Dinotefuran is a third-generation neonicotinoid pesticide and is increasingly used in agricultural production, which has adverse effects on nontarget organisms. However, the research on the impact of dinotefuran on nontarget organisms is still limited. Here the toxic effects of dinotefuran on an important economic species and a model lepidopteran insect, Bombyx mori, were investigated. Exposure to different doses of dinotefuran caused physiological disorders or death. Cytochrome P450, glutathione S-transferase, carboxylesterase, and UDP glycosyl-transferase activities were induced in the fat body at early stages after dinotefuran exposure. By contrast, only glutathione S-transferase activity was increased in the midgut. To overcome the lack of sensitivity of the biological assays at the individual organism level, RNA sequencing was performed to measure differential expressions of mRNA from silkworm larvae after dinotefuran exposure. Differential gene expression profiling revealed that various detoxification enzyme genes were significantly increased after dinotefuran exposure, which was consistent with the upregulation of the detoxifying enzyme. The global transcriptional pattern showed that the physiological responses induced by dinotefuran toxicity involved multiple cellular processes, including energy metabolism, oxidative stress, detoxification, and other fundamental physiological processes. Many metabolism processes, such as carbon metabolism, fatty acid biosynthesis, pyruvate metabolism, and the citrate cycle, were partially repressed in the midgut or fat body. Furthermore, dinotefuran significantly activated the MAPK/CREB, CncC/Keap1, PI3K/Akt, and Toll/IMD pathways. The links between physiological, biochemical toxicity and comparative transcriptomic analysis facilitated the systematic understanding of the integrated biological toxicity of dinotefuran. This study provides a holistic view of the toxicity and detoxification metabolism of dinotefuran in silkworm and other organisms. Graphical abstract: Image 1 Highlights: Dinotefuran significantly inhibited the growth and development of Bombyx mori. P450, GST, CarE and UGT are involved in dinotefuran detoxification. Dinotefuran inhibited fundamental metabolism and induced oxidative stress damage. Dinotefuran affected MAPK/CREB, CncC/Keap1 and PI3K/Akt signaling pathway.